2015
DOI: 10.1155/2015/453986
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cellular Metabolism Chemosensitizes the Doxorubicin-Resistant Human Breast Adenocarcinoma Cells

Abstract: Metabolic energy preferentially produced by glycolysis was an advantageous metabolic phenotype of cancer cells. It is also an essential contributor to the progression of multidrug resistance in cancer cells. By developing human breast cancer MCF-7 cells resistant to doxorubicin (DOX) (MCF-7/MDR cells), the effects and mechanisms of 2-deoxy-D-glucose (2DG), a glucose analogue, on reversing multidrug resistance were investigated. 2DG significantly inhibited the viability of MCF-7/MDR cells and enhanced DOX-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The significance of glycolysis has been increasingly demonstrated in many diverse cancers, including GC. Recent studies have revealed that increased glycolysis levels possibly contribute to the development of cancer cells [48][49][50][51][52] . For example, ENO1 enhances the level of glycolysis to promote GC cells' resistance to chemotherapy 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The significance of glycolysis has been increasingly demonstrated in many diverse cancers, including GC. Recent studies have revealed that increased glycolysis levels possibly contribute to the development of cancer cells [48][49][50][51][52] . For example, ENO1 enhances the level of glycolysis to promote GC cells' resistance to chemotherapy 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Anti-cancer treatments like radiation and chemotherapy can induce free radicals to kill cancer cells. Therefore, enhanced glycolysis may contribute to drug resistance by increasing reducing capacity [ 8 10 , 19 , 22 ]. In addition, the intracellular microenvironment affected by elevated glycolysis can turn to be lower glucose concentration with high levels of lactate, pyruvate and ATP, thus facilitating the development of multiple drug resistance (MDR) [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an energy-dependent transport protein, Pgp is involved in multi-drug resistance in cancer, and it further results in chemotherapy failure [ 35 ]. In the present study, immunofluorescence assay revealed that Pgp expression was significantly increased in the THC8307/Oxa cell line, but significantly decreased in both THC8307 and THC8307/Oxa cell lines after knocking-down PKM2/GLS1 expression.…”
Section: Discussionmentioning
confidence: 99%